Larval morphology of Arrenurus cuspidifer Piersig, A. claviger Koenike, and A. latus Barrois & Moniez (Acari: Hydrachnidia) - Zawal, Andrzej (Zootaxa, 2006)
The larva of Arrenurus latus is re-described and the larvae of A. cuspidifer and A. claviger are described for the first time. The larvae of A. cuspidifer and A. claviger share characters, such as shape of dorsal plate, shape of excretory pore plate and ratios of medial margins of coxal plates, which they also share with other Arrenurus s. str. species. In constrast, A. latus, a member of Micrarrenurus, lacks these characters. Instead, it closely resembles other members of Micrarrenurus such as Arrenurus albator, A. fimbraitus and A. crassicaudatus in having similar shape of dorsal plates, similar shape of excretory pore plates and pectinate setae on the PV3 and PV4 of the pedipalps. Therefore, the subgenus Micrarrenurus is further supported by characters of larval morphology.